Medicinal plants with teratogenic potential: current considerations - Kassiane Cristine da Silva Costa; Suzana Barbosa Bezerra; Clevanice Moreira Norte; Luciana Macatrão Nogueira Nunes; Tiago Moreira de Olinda (Universidade de São Paulo, 2012)
The aim of this study was to present the implications of the use of herbs during pregnancy, pointing out those that should be avoided during this condition because of their abortifacient and/or teratogenic potential. We carried out searches in the databases ScienceDirect, Scielo and Google Scholar, adopting as criteria for inclusion: book chapters and/or complete articles (with abstract), available in English, Portuguese or Spanish, published from 1996 to in 2011. After a pre-selection of 83 articles, 49 bibliographies were used in the manufacturing end of the article, where 25 were from the Scielo database, 18 from ScienceDirect and 6 from Google Scholar. From the articles studied, we identified the four most commonly used plants as emmenagogue/abortifacient agents by patients of the Department of Prenatal SUS: senne, arruda, boldo and buchinha-do-norte or cabacinha. Thus, we conclude that people often adhere to the maxim "if it's natural, it does no harm" in their rational use of natural products, without the right guidance, believing that these products are safe to use. This usage is even more worrisome among the elderly, pregnant women and children. Regarding the safety of these products, some information and reliable data are scarce or contradictory. Este trabalho busca as implicações atuais sobre o uso de plantas medicinais durante a gravidez, alertando sobre aquelas que devem ser evitadas nesse período por serem potencialmente abortivas e/ou teratogênicas. Para tanto, foram realizadas buscas nas bases de dados Sciencedirect, Scielo e Google scholar, adotando-se como critérios de inclusão capítulos de livros e/ou artigos completos (com abstract) e disponíveis, em português, inglês ou espanhol, publicados de 1996 a 2011. Após uma pré-seleção de 83 artigos, 49 bibliografias foram utilizadas na confecção final do artigo, sendo 25 provenientes da base de dados Scielo, 18 do Sciencedirect e 06 do Google scholar. A partir dos artigos estudados, identificaram-se as quatro plantas mais utilizadas como emenagogas/abortivas por pacientes do Serviço de Pré-Natal do SUS: senne, arruda, boldo e buchinha-do-norte ou cabacinha. Assim, é possível concluir que, muitas vezes, a população se utiliza da máxima "se é natural, não faz mal" para fazer uso irracional de produtos naturais, sem a correta orientação, acreditando que esses produtos sejam incapazes de provocar qualquer dano. Esse uso é ainda mais preocupante quando realizado por idosos, gestantes e crianças. Em relação à segurança do uso desses produtos, algumas informações e dados confiáveis ainda são escassos ou contraditórios.